Faktor Resiko Ulkus Diabetik Pada Penderita Diabetes Melitus - Kamaruddin, M.Yusril; Natsir, Pratiwi; Chaniago, Hendrian (Universitas Pahlawan Tuanku Tambusai, 2024)
In 2015, it was reported that around 415 million adults had diabetes, a 4-fold increase from 108 million in the 1980s. If there is no preventive action, this number will continue to increase without any decrease. It is estimated that by 2040 it will increase to 642 million sufferers. More than 415 million people worldwide have diabetes. The prevalence of diabetes continues to increase, and it is estimated that the number of people with diabetes will increase to 640 million by 2040. Currently, up to 1/4 of diabetes patients can experience leg ulcers, and at least a quarter of these ulcers do not heal, so these patients are at risk of amputation. The method used in this study was to review the literature using Google Scholar, National Center for Biotechnology Information (NCBI) & Research Science obtained 20 journals from the inclusion & exclusion criteria. The results of this study are that the risk factors for diabetic ulcers in patients with diabetes mellitus are multifactorial, including neuropathy, peripheral vascular disease, poor blood sugar control, obesity, smoking habits, old age, previous history of ulcers, and poor self-care. Based on this study, it is concluded that the more severe the wound experienced by patients with Diabetes Mellitus, the longer the wound healing time will be. It is possible that the feet of diabetic patients can be triggered by prolonged diabetes mellitus. Early detection or early screening of diabetic feet is needed by health services so that diabetic foot complications can be minimized.